Expressive Acts Realization in “I Care a Lot” Movie - Fanny Virginia; Zia Hisni Mubarak (LPPM Universitas Bumigora Mataram, 2021)
Realization of expressive acts is a phenomenon of pragmatics that appears in a movie. This descriptive qualitative research aimed at examining the types of expressive acts and how the expressive acts were realized in the movie. In collecting the data, this research implemented the observational method and non-participatory technique. Pragmatic identity method and pragmatic competence- in equalizing technique were applied as the method and technique of analyzing the data. Regarding the theory, this research applied expressive acts theory carried out by Searle and Vanderveken (1985). The findings revealed that there were 36 data of expressive act in the utterances of the characters. Those were 7 data of apologizing, 1 data of welcoming, 1 data of congratulating, 1 data of condoling, 1 data of greeting, 7 data of thanking, 5 data of complaining, 12 data of complimenting, and 1 data of deploring. The type of complimenting became the dominant type among other types. It is as a result of the existence of the rich elderly and their wealth that persuaded other characters to express complimenting.